SCIENTIFIC AND THEORETICAL ANALYSIS OF PROFESSIONAL COMPETENCE IMPROVEMENT OF FUTURE MILITARY PERSONNEL - Amonov Nurali Abduakhatovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article presents specific features of professional competence formation in future military personnel, information on the development of professional competence, as well as scientifically and theoretically based information on the conditions and opportunities included in the content of competence.